A Critical Performativity Analysis of Religious Laws on Homosexual Discourse in Nigeria: A Study of “Under The Udala Trees” and “Born On A Tuesday” - Oriola, Titilope Oluwaseun (Àgídìgbo: ABUAD Journal of the Humanities, 2024)
This manuscript delves into the ideological underpinnings embedded in the traditional religious doctrines governing homosexuality. Leveraging insights from a curated selection of Nigerian literary works, it illuminates the thematic intersections of Christianity and Islam, seeking to unravel the symbolic nuances of Biblical and Quranic precepts on homosexuality. This exploration asserts that these ancient laws stand detached from the diverse sexual orientations prevalent in contemporary society. While there exists a rich tapestry of discourse encompassing aspects such as LGBTQ+ rights and identity formation, a significant void remains in the scholarly exploration of the religious dimensions of homosexuality. Addressing this lacuna, essential in shaping informed gay law policies in the African context. Drawing upon the seminal theories of Judith Butler’s “Gender Performativity” (1990) and Fairclough’s “Critical Discourse Analysis” (1995) as analytical lenses, this paper scrutinises two poignant literary narratives – “Under the Udala Trees” and “Born on a Tuesday”- offering a deep dive into the religious discourse on homosexuality they encapsulate. The findings illuminate the overarching universal ethos present in the reversed texts of Bible and Quran, evincing a grand design that accommodates the multifaceted tapestry of human behavior of sexual orientations. It compellingly argues that the homophobic undertones discernible in these texts are emblematic, anchored in historical contexts, rather than prescriptive mandates for the modern era.